2009
DOI: 10.1038/nature07863
|View full text |Cite
|
Sign up to set email alerts
|

piggyBac transposition reprograms fibroblasts to induced pluripotent stem cells

Abstract: Transgenic expression of just four defined transcription factors (c-Myc, Klf4, Oct4 and Sox2) is sufficient to reprogram somatic cells to a pluripotent state. The resulting induced pluripotent stem (iPS) cells resemble embryonic stem cells in their properties and potential to differentiate into a spectrum of adult cell types. Current reprogramming strategies involve retroviral, lentiviral, adenoviral and plasmid transfection to deliver reprogramming factor transgenes. Although the latter two methods are transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
1,091
1
29

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,634 publications
(1,161 citation statements)
references
References 29 publications
11
1,091
1
29
Order By: Relevance
“…To meet this need, several nonintegration systems and removable systems have been developed. These include episomal vectors (Yu et al, 2009), the piggyBac transposon system (Kaji et al, 2009;Woltjen et al, 2009;Yusa et al, 2009), and minicircle vectors (Jia et al, 2010).…”
Section: Viral-free Approaches That Do Not Cause Genetic Alterationmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet this need, several nonintegration systems and removable systems have been developed. These include episomal vectors (Yu et al, 2009), the piggyBac transposon system (Kaji et al, 2009;Woltjen et al, 2009;Yusa et al, 2009), and minicircle vectors (Jia et al, 2010).…”
Section: Viral-free Approaches That Do Not Cause Genetic Alterationmentioning
confidence: 99%
“…Although iPSCs can be obtained by removable transposon or the non-integration episomal system, all of these methods still involve introducing foreign DNA into the cell so that the resulting cell lines need to be sequenced to verify that they are indeed free of genome alteration (Kaji et al, 2009;Woltjen et al, 2009;Yu et al, 2009). Thus, a reprogramming approach that does not use any DNA is highly desirable.…”
Section: Generation Of Ips Cells Using Proteins or Mrnas Of Defined Fmentioning
confidence: 99%
“…In addition, the viral vectors after integration with the host may lead to unexpected genetic disorder (Okita et al 2007;Takahashi et al 2007;Tateishi et al 2008;Yu et al 2009). Therefore, new and improved methods of generating iPS cells, including minimal or no genetic modification are needed (Huangfu et al 2008;Kaji et al 2009;Okita et al 2008;Stadtfeld et al 2008;Woltjen et al 2009;Yu et al 2009;Zhou et al 2009). Tateishi et al (2008) reported that iPS cells derived from human skin fibroblast by retroviral expression of OCT4, SOX2, c-MYC, and KLF4 have the potential to differentiate into insulin-producing islet-like clusters (ILCs).…”
Section: Differentiation Of Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…14 Many groups have now shown that somatic cells can be reprogrammed by overexpression of variable sets of few transcription factors in cells that share various characteristics with ESCs. [14][15][16][17] To date, several novel reprogramming protocols are available, [18][19][20][21][22] which have broadened the spectrum of cell types and species involved in iPSCs generation. Similar to ESCs, iPSCs also show the potential for differentiation into numerous cell types.…”
Section: Stem Cells and Sourcesmentioning
confidence: 99%